BIOPSY PROVEN ACUTE TUBULAR NECROSIS DUE TO RHABDOMYOLYSIS IN A DENGUE FEVER PATIENT: A CASE REPORT AND REVIEW OF LITERATURE - Repizo, Liliany P.; Malheiros, Denise M.; Yu, Luis; Barros, Rui T.; Burdmann, Emmanuel A. (Revista do Instituto de Medicina Tropical de São Paulo, 2014)
Renal histology results are very scarce in dengue-associated rhabdomyolysis patients developing acute kidney injury (AKI). We report a case of dengue fever-induced AKI associated to rhabdomyolysis with a renal biopsy showing acute tubular necrosis (ATN) and renal deposition of myoglobin. A 28-year-old patient who presented dengue fever (DF) complicated by severe AKI and rhabdomyolysis is described. The patient required hemodialysis for three weeks. A renal biopsy revealed ATN with positive staining for myoglobin in the renal tubuli. The patient was discharged with recovered renal function. In conclusion, this case report described a biopsy proven ATN associated to DF-induced rhabdomyolysis, in which renal deposition of myoglobin was demonstrated. We suggest that serum creatine phosphokinase should be monitored in DF patients to allow for an early diagnosis of rhabdomyolysis and the institution of renal protective measures.